2008
DOI: 10.1080/09273940802023810
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Lymphoma Masquerading as Vogt-Koyanagi-Harada Syndrome

Abstract: Intravascular lymphoma can present as a masquerade of VKH syndrome. Diagnosis can be aided with measurement of LDH and skin biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Although both VKH and SO have similar clinical manifestations, the diseases may prove to have different etiology. In patients with VKH, associations with other autoimmune disorders and malignancies have been reported among dark-skinned individuals [3][4][5][6][7][10][11][12]. In this study, we found two cases of choroidal malignant melanoma among patients with VKH.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although both VKH and SO have similar clinical manifestations, the diseases may prove to have different etiology. In patients with VKH, associations with other autoimmune disorders and malignancies have been reported among dark-skinned individuals [3][4][5][6][7][10][11][12]. In this study, we found two cases of choroidal malignant melanoma among patients with VKH.…”
Section: Discussionsupporting
confidence: 54%
“…The disease may be associated with signs of meningeal irritation with or without auditory disturbances and skin changes. Associations with other autoimmune disorders and malignancies have been reported [3][4][5][6][7][8][9][10][11]. The clinical manifestations of VKH are well outlined and the exact etiology of this condition remains to Electronic supplementary material The online version of this article (doi:10.1007/s00417-011-1727-4) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Intraocular lymphoma can arise primarily within the CNS, where it is either primary intraocular lymphoma or primary CNS lymphoma or from outside the CNS with ocular metastasis [9,76,83,[94][95][96][97]. Regardless of the origin, intraocular lymphoma tends to present bilaterally (80%) as either an intermediate and/or posterior uveitis.…”
Section: Grillo Levinson and Gordonmentioning
confidence: 99%
“…HIV testing should also be considered in otherwise healthy individuals presenting with suspected endogenous endophthalmitis. Other important considerations in the differential diagnosis are masquerade syndromes and primary intraocular B-cell lymphoma [10,76,94].…”
Section: Reviewmentioning
confidence: 99%
“…All reported cases of ophthalmologic IVLBCL have involved other organ systems or were not completely staged to rule out systemic involvement [4][5][6][7][8][9][10][11]. Most cases of ophthalmologic IVLBCL were not diagnosed by biopsy of an ophthalmologic structure, but at either autopsy or the patient's ophthalmologic signs and symptoms were correlated with eye involvement after a biopsy of another organ system established the diagnosis.…”
Section: Introductionmentioning
confidence: 99%